A comparative analysis of legal aspects of electronic contracts in Brazil. (1st April 2011) - Rohrmann, Carlos Alberto; Campos, Miriam De Abreu Machado e
This article presents a comparative analysis of some of the legal aspects of contracts for electronic commerce in Brazil. The article studies the theoretical bases of the legal systems that have influenced Brazilian contract law. The first part analyses the formation of contracts under the terms of the civil code. The second part looks at contracts under consumer law. The article applies the concepts of Brazilian contract law to the specifics of the regulation of electronic contracts, and addresses the regulation of electronic contracts in Brazil from historical and comparative perspectives. We will demonstrate how legal concepts pertaining to private contracts have evolved in Brazil, from the classical theory to the present. As Brazilian law was highly influenced by both German and French law in the 19th century, we will give a brief comparative analysis of the influence of both legal systems on the regulation of private contract law in Brazil. Finally, the article looks at aspects related to offer and acceptance of electronic contracts, the place of contract and the consumer's right to cancel a contract.